The idea of Human Development in the Venezuelan Constitution of 1999 (Mayéutica Revista Científica de Humanidades y Artes, 2018)
The phrase human development, unprecedented in the history of the Venezuelan constitutions, appears twice in the 1999 Constitution, in articles 112 and 299, both precepts inserted between the clauses that make up the so-called Economic Constitution. The constitutional text does not define the linguistic formula, nor does its Explanatory Memorandum. The primary task of this essay is to provide an approximation of the meaning of the term human development, as a contribution to its understanding and function in the 1999 constitutional text. The working papers of the Economic and Social Commission of the National Constituent Assembly of 1999, which are based in the Historical Archive of the National Assembly, were very useful in their implementation. Using tools of constitutional interpretation as a method, and on the basis of the Social State as a hermeneutic criterion, the author presents this booklet as an attempt to clarify the idea of human development immersed in the current constitutional text.
Keywords: Constitution of the República Bolivariana de Venezuela; democratic and social state of law and justice; Human Development